PERAN TUKANG BATU TERHADAP PENYELESAIAN KANTOR MUKIM DAN KEUCIK KABUPATEN ACEH UTARA - Chairil Anwar (Politeknik Negeri Lhokseumawe, 2013)
Construction projects involve many parties in it, among which is not less important is tukangTukang a person who has specific expertise and skills in work productivity due to experience and practice, but is stil fimited to simple jobs such as brick Pasangaan, Plesteran. Metode that the author did with descriptive the direct field observation during handyman work ranging fom mixing sand, cement, water to become mortal and interesting thread for mounting the brick so the results are really straight either horizontally or vertically, taking the measurements the work / productivity generated by an every day from each location assisted by field supervisors (consultants). study aimed to find out how the length of time an installation of brick and stucco building with knowing the time of installation per meter width or seek productivity per day. Based tiori Soedrajat (1984), together with the volume of work productivity divided by time.